Tafsir al Jalalayn In Contemporary Islamic Scholarship - Iin Parninsih; Muh Alwi HS; Asmullah A; Imran Anwar Kuba (The International Journal of Pegon : Islam Nusantara civilization, 2026)
This study systematically examines the role of Tafsir al-jalalayn in contemporary Islamic scholarship, highlighting its ongoing relevance in intellectual, social, and religious spheres. The tafsir is viewed not merely as a foundational text but as a dynamic medium fostering interdisciplinary dialogue. Employing a systematic literature review methodology, the study analyzes 17 national and international journal articles from 2000 to 2025. The findings demonstrate that Tafsir al-jalalayn possesses strong resilience in addressing the intellectual and social challenges faced by today’s Muslim communities. The shift from a descriptive-historical focus to a more contextual and reflective approach affirms that this tafsir is a continually reinterpreted source of knowledge, strengthening its position both in academia and religious practice, in traditional settings such as pesantren and the broader digital realm. It plays a central role in bridging classical scholarly authority with the realities of modern Muslim societies. The potential for further research development remains open, especially through interdisciplinary approaches and social orientation. The integration of manuscript studies, education, and modern media presents promising opportunities for relevant and productive future research. Thus, this study underscores the importance of interdisciplinary development and technological integration in Tafsir al-jalalayn studies to reinforce its social and religious relevance and promote inclusive dialogue between classical tradition and the challenges of contemporary Muslim communities, ensuring the tafsir remains a vital part of Islamic intellectual dynamics. Penelitian ini mengkaji secara sistematis peran Tafsir al-jalalayn dalam kajian keislaman kontemporer, menyoroti relevansi berkelanjutan dalam ranah intelektual, sosial, dan keagamaan. Tafsir ini dipandang bukan hanya sebagai teks dasar, tetapi sebagai medium dinamis yang mendorong dialog interdisipliner. Dengan metodologi tinjauan literatur sistematis, studi menganalisis 17 artikel jurnal nasional dan internasional (2000–2025). Hasil menunjukkan Tafsir al-jalalayn memiliki daya lenting kuat dalam menghadapi tantangan intelektual dan sosial umat Islam saat ini. Perkembangan kajian dari fokus deskriptif-historis ke pendekatan kontekstual dan reflektif menegaskan tafsir ini sebagai sumber ilmu yang terus dimaknai ulang, memperkuat posisinya dalam akademik dan praktik keagamaan, baik di pesantren maupun ranah digital. Tafsir ini berperan sentral menjembatani otoritas keilmuan klasik dengan realitas umat Islam modern. Potensi pengembangan kajian masih terbuka, terutama melalui pendekatan lintas disiplin dan orientasi sosial. Integrasi kajian naskah, pendidikan, dan media modern membuka peluang riset lanjutan yang relevan dan produktif. Dengan demikian, penelitian ini menegaskan pentingnya pengembangan lintas disiplin dan integrasi teknologi dalam kajian Tafsir al-jalalayn guna memperkuat relevansi sosial dan keagamaan serta mendorong dialog inklusif antara tradisi klasik dan tantangan umat Islam modern, sehingga tafsir ini layak terus dikaji dan dihidupkan sebagai bagian dari dinamika intelektual Islam.